Genotypic variation in the response of soybean to elevated CO2 - Soares, José C.; Zimmermann, Lars; Zendonadi dos Santos, Nicolas; Muller, Onno; Pintado, Manuela; Vasconcelos, Marta W. (Plant-environment interactions (Hoboken, N.J. : 2018), 2021)
The impact of elevated CO2 (eCO2) on soybean productivity is essential to the global food supply because it is the world's leading source of vegetable proteins. This study aimed to understand the yield responses and nutritional impact under free‐air CO2 enrichment (FACE) conditions of soybean genotypes. Here we report that grain yield increased by 46.9% and no reduction in harvest index was observed among soybean genotypes. Elevated CO2 improved the photosynthetic carbon assimilation rate, leaf area, plant height, and aboveground biomass at vegetative and pod filling stages. Besides the positive effects on yield parameters, eCO2 differentially affected the overall grain quality. The levels of calcium (Ca), phosphorous (P), potassium (K), magnesium (Mg), manganese (Mn), iron (Fe), boron (B), and zinc (Zn) grain minerals decreased by 22.9, 9.0, 4.9, 10.1, 21.3, 28.1, 18.5, and 25.9% under eCO2 conditions, respectively. Soluble sugars and starch increased by 9.1 and 16.0%, respectively, phytic acid accumulation increased by 8.1%, but grain protein content significantly decreased by 5.6% across soybean genotypes. Furthermore, the antioxidant activity decreased by 36.9%, but the total phenolic content was not affected by eCO2 conditions. Genotypes, such as Winsconsin Black, Primorskaja, and L‐117, were considered the most responsive to eCO2 in terms of yield enhancement and less affected in the nutritional quality. Our results confirm the existence of genetic variability in soybean responses to eCO2, and differences between genotypes in yield improvement and decreased sensitivity to eCO2 in terms of grain quality loss could be included in future soybean selection to enable adaptation to climate change. ‐ Intraspecific variation among soybean genotypes affect the responses under eCO2conditions.‐ eCO2 significantly increased soybean yield.‐ Grain quality was affected by CO2 enrichment.